2019
DOI: 10.1002/pc.25365
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical postbuckling of pressure‐loaded CNT‐reinforced composite cylindrical shells under tangential edge constraints and various temperature conditions

Abstract: Buckling and postbuckling behavior of carbon nanotube‐reinforced composite (CNTRC) cylindrical shells with tangentially restrained edges exposed to preexisting temperature conditions and subjected to uniform external pressure are presented in this analytical study. Three temperature conditions considered are that uniform temperature rise, through‐the‐thickness temperature gradient, and in‐plane linear temperature distribution. Carbon nanotubes (CNTs) are reinforced into matrix phase through uniform or function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Previous investigations on FGM structures [25–29] indicated that tangential constraints of boundary edges have dramatic influences on type of buckling response and postbuckling load carrying capability of FGM plates and shells. Recent studies on FG-CNTRC structures [3039] demonstrated impressive effects of tangential edge restraints on the nonlinear stability of nanocomposite plates and shells subjected to mechanical, thermal, and thermomechanical loads. In spite of numerous investigations on FGM structures, to the best of authors’ knowledge, there is an evident lack of studies on nonlinear stability of FGM sandwich cylindrical shells with tangentially restrained edges in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on FGM structures [25–29] indicated that tangential constraints of boundary edges have dramatic influences on type of buckling response and postbuckling load carrying capability of FGM plates and shells. Recent studies on FG-CNTRC structures [3039] demonstrated impressive effects of tangential edge restraints on the nonlinear stability of nanocomposite plates and shells subjected to mechanical, thermal, and thermomechanical loads. In spite of numerous investigations on FGM structures, to the best of authors’ knowledge, there is an evident lack of studies on nonlinear stability of FGM sandwich cylindrical shells with tangentially restrained edges in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The linear and nonlinear behavior of cylindrical shell made of other advanced composites has been published by many authors in recent years, however, the researches on the stiffened GRC cylindrical shells are still very limited. Thermomechanical postbuckling and vibration analysis of carbon nanotube‐reinforced composite cylindrical shells were studied by Hieu and Tung [ 29 ] and Baharali and Yazdi. [ 30 ] Additionally, the mechanical behavior of carbon nanotube‐reinforced composite and graphene‐reinforced composite conical shell was also studied by Hajmohammad.…”
Section: Introductionmentioning
confidence: 99%
“…By using the Galerkin method, the buckling and postbuckling behavior of CNT-reinforced cylindrical shells under axial compression, external pressure and thermal load was investigated. [15][16][17][18] Vibration responses of CNTreinforced cylindrical shells were also investigated [19][20][21][22] by different methods with the temperature-dependent material properties, 19 with the uniformly distributed temperature, 20 with hybrid laminated structures, 21 and with viscoelastic foundation-shell interaction. 22 The dynamic seismic responses of CNT-reinforced cylindrical shells considering the viscoelastic effects in moisture 23 or hygrothermal 24 environments were performed.…”
Section: Introductionmentioning
confidence: 99%